2021
DOI: 10.3390/app11125738
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Properties, Cytotoxic Effects, and Fatty Acids Composition of Vegetable Oils from Purslane, Linseed, Luffa, and Pumpkin Seeds

Abstract: In the present study, the antimicrobial and cytotoxic activities, as well as the fatty acids composition in vegetable seed oils from linseed, purslane, luffa, and pumpkin were evaluated. For this purpose, two linseed oils and one luffa oil were commercially obtained, while purslane and pumpkin oils were obtained from own cultivated seeds. The results showed a variable fatty acids composition among the tested oils, with α-linolenic, linoleic, oleic, palmitic, and stearic acid being the most abundant compounds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…As for its antifungal properties, it proved more effective against Aspergillus versicolor, Aspergillus niger, Penicillium funiculosum, and Penicillium verrucosum var. cyclopium than the positive controls (E211 and E224) (Petropoulos et al, 2021). PSO can inhibit the growth of Aeromonas veronii, Candida albicans, Enterococcus feacalis, E. coli, Salmonella enterica, Typhimurium, and S. aureus (Hammer et al, 1999;Syed et al, 2019).…”
Section: Antimicrobial Activitymentioning
confidence: 86%
See 1 more Smart Citation
“…As for its antifungal properties, it proved more effective against Aspergillus versicolor, Aspergillus niger, Penicillium funiculosum, and Penicillium verrucosum var. cyclopium than the positive controls (E211 and E224) (Petropoulos et al, 2021). PSO can inhibit the growth of Aeromonas veronii, Candida albicans, Enterococcus feacalis, E. coli, Salmonella enterica, Typhimurium, and S. aureus (Hammer et al, 1999;Syed et al, 2019).…”
Section: Antimicrobial Activitymentioning
confidence: 86%
“…As for its antifungal properties, it proved more effective against Aspergillus versicolor , Aspergillus niger, Penicillium funiculosum , and Penicillium verrucosum var. cyclopium than the positive controls (E211 and E224) (Petropoulos et al., 2021).…”
Section: Biological Activitymentioning
confidence: 99%
“…The main unsaturated fatty acids of purslane oil were oleic 20.23%, linoleic 42.82% and linolenic 33.60% acids. Petropoulos et al (2021) found that purslane seed oil was a rich source of linoleic (34.10%) and linolenic (41.25%) acids with minor content of oleic acid (5.24%). Dubois et al (2007) reported a slightly lower content of α-linolenic acid (32.4%) than linoleic acid (34.1%).…”
Section: Physicochemical Properties and Fatty Acid Composition Of Pur...mentioning
confidence: 99%
“…The increase in demand for functional foods, made up of biologically and physiologically active compounds that provide health benefits, has increased considerably (Konstantinidi & Koutelidakis, 2019; Ramakrishna et al, 2020). In this scope, recent studies have shown that, in addition to their nutritional capacity, seeds and almonds are potential resources for obtaining health‐beneficial oils (Chew et al, 2021; Petropoulos et al, 2021; Teng et al, 2017; Teng & Chen, 2017). Babassu ( Orbignya phalerata Mart., Arecaceae) is an important palm tree native to Brazil, specifically the Amazon (Companhia Nacional de Abastecimento, 2017).…”
Section: Introductionmentioning
confidence: 99%